U.S. – RUSSIA RELATIONS AND ARMS CONTROL: BREATING THE CLINCH - N. I. Bubnova (Vestnik MGIMO-Universiteta)
The article examines the new U.S. administration’s outlook on arms control, analyses the existing problems in this field and possible ways for their resolution, compares Donald Trump’s statements on military and political issues with the president’s first steps in this area, and offers forecasts and recommendations on the prospects for U.S.-Russia cooperation in arms limitations and reductions. The author proceeds from the assumption that arms control is a key component in measures to ensure international security. Even if the current tense U.S.- Russian relations provide little room for maneuver and the internal political struggle in DC sets limits on the possible bilateral measures, Moscow should nevertheless take initiative in putting forward a set of proposals to reduce weapons, especially in the very sensitive and risk-prone nuclear field. This will allow in future negotiations to proceed from options that will take into account Russian interests and the specifics of Russia’s weapons systems, while at the same time showing the resolve of the nuclear superpowers to reduce existing threats through negotiations and leading the way for other countries to join. Taking into account the importance of arms control, all efforts should be made to enforce the existing treaties, consolidate the current international treaty-based legal system, and work further on new arms control and arms reduction agreements.